Męczennicy Afryki Północnej w Martyrologium Rzymskim - Nocoń, Arkadiusz (Vox Patrum, 2019)
As is commonly known, Christianity reached the territories of North Africa relatively early, and its development was so dynamic that it surprises historians. In seeking an explanation of this phenomenon, many point to the line of one of its representatives, Tertullian: “the blood of the martyrs is the seed of Christians”. If that was the case, how many martyrs were there in the African Church? In which period and for what reason were they killed? Answers to these and other questions were searched for in the Roman Martyrology, a book that essentially is liturgical, but also contain some documentary elements. This study has led to a deepening of our knowledge of the martyrs of North Africa as it gave some at least general information about the time of the persecutions, the cities in which they took place, the numbers of the martyrs, their social status, and above all about their attitude in the face of death that in most cases was cruel. This information is precious, not only because martyrdom is a key factor for the understanding of Christian antiquity, but also because it is rarely mentioned in historical publications of our country.